Active Home Literacy Environment: parents' and teachers' expectations of its influence on affective relationships at home, reading performance, and reading motivation in children aged 6 to 8 years - Romero González, Marta; Lavigne-Cerván, Rocío; Gamboa-Ternero, Sara; Rodríguez-Infante, Gemma; Juárez-Ruiz-de-Mier, Rocío; Romero-Pérez, Juan Francisco (Frontiers Media, 2023)
Studies highlight the benefits of active Home Literacy Environment on learning and reading habits. This model is based on harnessing family involvement, resources and capabilities to create learning opportunities around reading, engaging in practices related to written language at home. However, it is less common to find applied research with children from the age of six, with older ages and already initiated in reading decoding. The aims are confirming and improving the expectations of families and teachers of a group of children (6–8 years old) regarding the effect of an active Home Literacy Environment program on the improvement of affective relationships between parents and children, reading performance, and children’s reading motivation. The method and procedure followed included carrying out an active Home Literacy Environment program for 18 months with a group of children (aged 6 to 8 years), their families and their teachers, and measures of all variables were collected at four times, using an Ad Hoc instrument designed for families and teachers. The results show that participants had high expectations about the influence of the Home Literacy Environment on the improvement of all variables even before the implementation of the program, improving their expectations about its effects on positive affective relationships at home and on reading achievement after the intervention. In conclusion, we suggest the need to continue investigating the effects of the active Home Literacy Environment program applied to children aged 6 to 8 years, older than those traditionally investigated. As well as their effects on family relationships, reading ability, and reading motivation.
Keywords: Lectura - Psicología; Alfabetización; Home literacy environment; Reading; Motivation; Affective relationships; Primary education; Program